Susceptibility to Leishmania major infection in mice: multiple loci and heterogeneity of immunopathological phenotypes - Lipoldová, M; Svobodová, M; Krulová, M; Havelková, H; Badalová, J; Nohýnková, E; Holán, V; Hart, A A; Volf, P; Demant, P (Genes and immunity, 2000)
Susceptibility as opposed to resistance of mouse strains (e.g., BALB/c vs C57BL/6) to Leishmania major has been attributed to a defective Th1 and a predominant Th2-response, resulting in increased IL-4 and IgE production, and decreased interferon gamma (IFN gamma) production, macrophage activation and elimination of parasites. Here we report dissection of genetic and functional aspects of susceptibility to leishmaniasis using two contrasting inbred strains BALB/cHeA (susceptible) and STS/A (resistant) and a resistant Recombinant Congenic (RC) Strain, CcS-5/Dem, which carries a random set of 12.5% of genes from the strain STS and 87.5% genes from the susceptible strain BALB/c. Linkage analysis of F2 hybrids between the resistant RC strain CcS-5 and the susceptible strain BALB/c revealed five loci affecting the response to the infection, each apparently associated with a different combination of pathological symptoms and immunological reactions. The correlation between Th2-type immune reactions and the disease in the F2 mice was either absent, or it was limited to mice with specific genotypes at loci on chromosomes 10 and 17. This suggests that the resistance vs susceptibility is influenced by mechanisms additional to the postulated antagonistic effects of Th1 and Th2 responses, and that the host's genotype affects the development of leishmaniasis in a complex way.
Keywords: druhová specificita; fenotyp; Phenotype; Genotype; polymorfismus genetický; Th1 buňky; Lymphocyte Activation; techniky in vitro; myši inbrední BALB C; Leishmaniasis, Cutaneous; Th1 Cells; Species Specificity; Polymorphism, Genetic; Genetic Linkage; aktivace lymfocytů; Mice, Inbred BALB C; Animals; ženské pohlaví; genetická vazba; Leishmania major; zvířata; Th2 Cells; leishmanióza kožní; myši inbrední C57BL; Hybridization, Genetic; myši; inbrední kmeny myší; Mice, Inbred C57BL; Th2 buňky; genotyp; hybridizace genetická; Mice; Female; zvířata kongenní; Mice, Inbred Strains; Animals, Congenic; In Vitro Techniques